Analysis of the Correlation of Student Learning Outcomes with Motivation (Case Study at SMP Ar-Rahman Medan) - Hernawan Syahputra Lubis; Kamil; Dara Mayang Sari (International Journal of Society and Law, 2024)
The purpose of this study is to find a correlation between student learning outcomes and the motivation given by Islamic religious education teachers with a case study of Ar-Rahman Medan Junior High School. This research approach uses a qualitative model of correlational design. The population in this study was all students of Ar-Rahman Medan Junior High School, with samples taken using simple random sampling techniques. Data collection was carried out through questionnaires to measure the level of student learning motivation, as well as documentation of student learning outcomes. The results of the research conducted show that Islamic religious education teachers are very important in the teaching and learning process in schools, and Islamic religious education teachers must be able to overcome problems experienced by students in order to improve student learning outcomes. Data collection was carried out through questionnaires to measure the level of student learning motivation, as well as documentation of student learning outcomes. The results showed a positive and significant value between student learning outcomes and the provision of learning motivation at Ar-Rahman Medan Junior High School, with a correlation coefficient value of 0.71. The provision of learning motivation contributes 50.41% to student learning outcomes at Ar-Rahman Medan Junior High School.